Democracy and power : the Delhi lectures - Chomsky, Noam
Noam chomsky visited india in 1996 and 2001 and spoke on a wide range of subjects, from democracy and corporate propaganda to the nature of the world order and the role of intellectuals in society he captivated his audiences with his lucid challenge of dominant political analyses, the engaging style of his talks, and his commitment to social equality as well as individual freedom chomskys early insights into the workings of power in the modern world remain timely and compelling published for the first time, this series of lectures also provides the reader with an invaluable introduction to the essential ideas of one of the leading thinkers of our time about the author noam chomsky is an american linguist, philosopher, cognitive scientist, logician, political commentator and anarcho-syndicalist activist sometimes described as the father of modern linguistics, chomsky is also a major figure in analytic philosophy he has spent most of his career at the massachusetts institute of technology (mit), where he is currently professor emeritus, and has authored over 100 books he has been described as a prominent cultural figure, and was voted the worlds top public intellectual in a 2005 poll